Surveillance of listeriosis in the Tel Aviv District, Israel, 2010–2015. Issue 3 (8th January 2018) - Salama, M.; Amitai, Z.; Ezernitchi, A. V.; Sheffer, R.; Jaffe, J.; Rahmani, S.; Leshem, E.; Valinsky, L.
Abstract: This study analyses the epidemiologic, clinical and molecular findings of all culture-confirmed cases of listeriosis notified from 2010 to 2015 in the Tel Aviv District, which is known to have high rates of listeriosis. All clinical isolates of Listeria monocytogenes were subtyped using two-enzyme pulsed-field gel electrophoresis. During the studied period, 102 cases of listeriosis were notified, including 23 pregnancy-associated cases (23%). Among 79 non-pregnancy-associated cases, 18 had neuro-invasive disease (21%). There were 26 deaths associated with the disease. Using molecular identification, we found a number of clusters of identical bacterial clones, which pointed to possible sources of infection. The high rates of morbidity and mortality resulting from listeriosis, as well as the diverse ways of infection demonstrated in this study, accentuate the need to boost public health actions, in order to raise awareness and better control high-risk contamination routes.